Safety and efficacy of angioplasty with intracoronary stenting in patients with unstable coronary syndromes. Comparison with stable coronary syndromes - Correia,Luís C. L. (2000)
OBJECTIVE: To assess safety and efficacy of coronary angioplasty with stent implantation in unstable coronary syndromes. METHODS: Retrospective analysis of in-hospital and late evolution of 74 patients with unstable coronary syndromes (unstable angina or infarction without elevation of the ST segment) undergoing coronary angioplasty with stent placement. These 74 patients were compared with 31 patients with stable coronary syndromes (stable angina or stable silent ischemia) undergoing the same procedure. RESULTS: No death and no need for revascularization of the culprit artery occurred in the in-hospital phase. The incidences of acute non-Q-wave myocardial infarction were 1.4% and 3.2% (p=0.6) in the unstable and stable coronary syndrome groups, respectively. In the late follow-up (11.2±7.5 months), the incidences of these events combined were 5.7% in the unstable coronary syndrome group and 6.9% (p=0.8) in the stable coronary syndrome group. In the multivariate analysis, the only variable with a tendency to significance as an event predictor was diabetes mellitus (p=0.07; OR=5.2; 95% CI=0.9-29.9). CONCLUSION: The in-hospital and late evolutions of patients with unstable coronary syndrome undergoing angioplasty with intracoronary stent implantation are similar to those of the stable coronary syndrome group, suggesting that this procedure is safe and efficacious when performed in unstable coronary syndrome patients.